The 1999 eartquake activity in Izmit, NW Turkey. An opportunity for the study of actualistic strike-slip related tectonic forms - LEKKAS, E. L. (Bulletin of the Geological Society of Greece, 2001)
The 1999 earthquake activity in the area of Izmit - Bolu, Turkey, which included two major shocks, on the 17th Aug. and 12th Nov. 1999, was caused by the reactivation of fault segments that belong to NAFZ. Field research was focused on fault geometry and slip characteristics, and allowed us to distinguish seven successive right-stepping reactivated segments and the related oversteps. Investigations showed that there is good match between the observed structures and those produced by experimental modelling. Finally, an estimation is made as to the percentage of seismic and aseismic slip on the reactivated segment of the fault zone